Bringing Affect Back in: Measuring and Comparing Subjective Well-Being Across Countries - Fors, Filip; Kulin, Joakim (Social indicators research, 2016)
In recent years, researchers and policymakers have paid increasing attention to cross-country comparisons of subjective well-being. Whereas classical theories of quality of life emphasize the central role of affective well-being (i.e., whether a person feels good or bad), previous comparative studies have focused almost exclusively on life satisfaction (i.e., cognitive evaluations of life). This study brings affect into the comparative study of subjective well-being, constructing a new measurement instrument that captures both the affective and cognitive dimensions of subjective well-being. Using European Social Survey data and multi-group confirmatory factor analysis, we estimate latent country means for the two dimensions and compare country rankings across the two measures. The results reveal important differences in country rankings depending on whether one focuses on affective well-being or life satisfaction. We identify crucial differences among top-ranking countries and, perhaps even more importantly, considerable differences in rankings among more moderately ranking countries. In a second step, we compare and evaluate the single-item measures commonly used in previous research with the results based on our new measures. We conclude by discussing our results in relation to previous studies, and in terms of their possible implications for future research and for policymakers bent on improving national levels of subjective well-being.